Appreciative Inquiry Coaching untuk Menurunkan Stres Kerja - Agung Suprapto Dwi Cahyono; Koentjoro Koentjoro (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2015)
Many  factors such as individual, social, environment, organization and work characteristic factors  potentially raising stress.  The aim of this study was to examine the impact  of  appreciative inquiry coaching to reduce work stress of Traffic Policeman. The subjects of this study were Traffic Policeman at Yogyakarta. Experiment design was referred pretest-posttest control group design. Subject divided into two groups, experimental  group and control group. The experimental  group was the one who received appreciative inquiry coaching as treatment  and  waiting  list  for  control  group. The effectiveness  of coaching measured by Traffic Policeman Work Stress Scale that have been given for two groups of this study 3 weeks after  and before treatment. By using mixed-anova, the result indicated that Appreciative Inquiry Coaching reduced work stress of Traffic Policeman significantly (F=179.192, p<0.01).